Analisis Kesulitan Membaca Permulaan Siswa Kelas II SD Negeri 0501 Hutanopan - Era Mutiah; Nurhalimah Harahap; Risky Padilah (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Beginning reading ability is an important issue for low grade students. If students' reading ability cannot be completed, it will become a big problem at the next level. The purpose of this study was to determine (1) the reading ability of the second-grade students at SD Negeri 0501 Hutanopan. (2) What are the inhibiting factors for beginning reading comprehension difficulties for second grade students at SD Negeri 0501 Hutanopan. This research is presented in a qualitative descriptive form with the aim of describing a process that occurs in the field. Data collection techniques are observation, interviews, and documentation. Based on the results of the study it can be concluded that (1) the initial reading ability of class II students at SD Negeri 0501 Hutanopan on average the second grade students were quite good at reading, because there were still found 6 students only recognized letters without being able to combine letters into words, 16 students only can spell letters but difficult to combine letters, 10 students are quite good at combining letters. (2) There are two factors inhibiting the difficulty of beginning reading skills for second grade students at SD Negeri 0501 Hutanopan, namely internal and external.